Evaluasi Pengelolaan Limbah Bahan Berbahaya dan Beracun di PT. X Industri Plastik - Mila Dirgawati; Aulya Amitasyah (Journal Serambi Engineering, 2024)
PT X is one of the companies that generates hazardous waste from production and non-production activities. There are nine types of B3 waste generated, namely used oil, electronic waste, used batteries / feet, B3 contaminated mop, used B3 packaging, used refrigerant from electronic equipment, expired products / raw materials, materials / products that do not meet technical specifications and production residues. The purpose of the study is to determine the source, suitability of B3 waste management carried out by PT X and provide recommendations for improvement of non-compliant findings. This research uses primary data collection methods and secondary data. The results showed the percentage of the overall level of suitability of B3 waste management carried out by PT X obtained a value of 68.1% which means it is included in the "good" category. Recommendations for improvement that can be given are that the packaging needs to be given a symbol that matches its characteristics and a label on each hazardous waste packaging found at PT. X and using closed conveyance so that it can load category 1 and category 2 B3 waste simultaneously by considering the compatibility of B3 waste.